EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK TOKEN ECONOMY UNTUK MENINGKATKAN KEDISIPLINAN SISWAKELAS XII SMAS MUHAMMADIYAH 1 BAUBAU - Arifin, Andrianto; Sammaila, Baharuddin; Arfah, Aryati (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of the study was to test the effectiveness of group guidance using the token economy technique in improving student discipline. The research method used is quantitative research with experimental research methods with Quasi Experimental Design: non-equivalent control group design. The research population was 84 students with a sample of 24 students. The results obtained are the general profile of the discipline of class XII students of SMAS Muhammadiyah 1 Baubau in the experimental group is in the low category, meaning that students are less disciplined in the sense that students violate school rules a lot. After the treatment was held by conducting group guidance with the token economy technique and several stages of its implementation, there was an increase in the discipline score in the low category to the medium category, meaning that student discipline had increased. So, it can be concluded that the guidance of the token economy technique group can improve the discipline of class XII students of SMAS Muhammadiyah 1 Baubau. This is because the token economy technique is very helpful in improving student discipline by using the characteristics of class attendance, carrying out picket assignments, arriving on time, and complying with school school regulations